Effect of gender and exercise on haematological and biochemical parameters in Holsteiner horses. Issue 5 (8th January 2017) - Andriichuk, A.; Tkachenko, H.
Summary: The objective of this study was to assess the influence of exercise of average intensity in the haematological and biochemical values, as well as acidic resistance of erythrocytes in mares and stallions of Holsteiner breed. A total of seventeen horses of Holstein breed (seven mares and 10 stallions aged 6 years) were used in this study. The blood samples were assessed for haematocrit (HCT) value, haemoglobin concentration (HGB), the amount of red blood cells (RBC), white blood cells (WBC), platelets (PLT), leucogram, mean corpuscular haemoglobin concentration (MCHC), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), red cell distribution width (RDW) and platelet distribution width (PDW). Serum concentrations of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and lactate dehydrogenase (LDH) as well as oxidative stress biomarkers were analysed. Stallions showed a significant increase in leucocytes and granulocytes amount, as well as erythrocytes, haemoglobin and haematocrit levels after exercise test. Pre‐exercise level of mean corpuscular haemoglobin concentration was higher in stallions. At the same time, mares showed significant decrease in platelet volume after exercise test. Physical effort in stallions leads to significant increase in aspartate aminotransferase activity. Trained mares and stallions showed a decrease in lipid peroxidation after exercise. Exercise also caused increase in oxidative modified protein of erythrocytes in stallions indicating by exercise‐induced oxidative stress. The resistance of erythrocytes in 0.1 m HCl was similar between females and males. No statistically significant differences in the percentage of haemolysed erythrocytes before and after exercise were observed.